Black-White Ethnic Differences In Identification With The Work Ethic: Some Implications For Organizational Integration - Bhagat, Rabi S. (Academy of Management Review, 1979)
Literature discussing the social role training and occupational readiness of American blacks for their propensity to identify with the four themes of the work ethic is reviewed. The findings are incorporated within a new conceptual model. It depicts the mechanism of how black ethnic values, coupled with negative job experiences, prevent a large majority of the black population from strongly identifying with the work ethic. Implications for organizational policy and the utility of culture-assimilator training for bringing about the necessary organizational integration are discussed.